Pengembangan Media Poster Digital Dalam Pencegahan Kekerasan Seksual Pada Remaja di SMA Negeri 5 Surakarta - Feliksita Karolina Kahre (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Sexual violence is any act of humiliating, insulting, attacking, and/or other acts against a person’s body, sexual desires and/or reproductive function by force. This form of sexual violence can occur in everyday interactions among teenagers, including when they start having relationships with the opposite sex. This can be minimized in various ways, one of which is by providing motivation for teenagers to prevent acts of sexual violence. Motivation given to teenagers can be in the form of learning media, one of which is digital poster media. Digital poster media is more effective as an outreach medium because it helps stimulate the sense of sight, the visual aspect of poster images makes it easier to receive information. The aim of this research is to determine the development of digital poster media in preventing sexual violence against teenagers at Senior High School 5 Surakarta. This research method uses Research and Development (R&D), with the ADDIE model being developed in 5 stages, namely (Analysis, Design, Development, Implementation, Evaluation). The results of this research obtained an assessment of digital poster media from material experts 96%, media experts 67%, small scale trials 83.3%, and field trials 83.83%, so it can be concluded that the media developed is "very feasible" to be used in preventing sexual violence against teenagers at Senior High School 5 Surakarta